Diabetic Neuropathic Cachexia: A Clinical Case and Review of Literature - Alessio Bellelli; Daniele Santi; Manuela Simoni; Carla Greco (Life, 2022)
A 46-year-old man was admitted to the surgical department because of abdominal pain and anemia, with the radiological finding of a perforated duodenal ulcer, and underwent laparoscopic surgical treatment. Type 2 diabetes mellitus (T2DM) had been diagnosed 5 years earlier and treated with diet. At clinical investigation, the patient was depressed and anorexic; moreover, he complained of lower extremity weakness and bilateral feet pain, burning in nature and accompanied by allodynia. This painful sensation had been preceded by an 8-month history of fatigue and anorexia with profound weight loss of 35 kg. After clinical evaluation and a nerve conduction study, diagnosis of diabetic cachectic neuropathy was made based on the rapid onset of severe neuropathic pain in the context of diabetic neuropathy, marked weight loss, and depressed mood. The therapy with pregabalin and duloxetine had scarce effect and was gradually discontinued. The patient, however, obtained progressive relief and amelioration of neuropathic lower-limb pain concomitant with weight gain. This clinical trend also confirmed the diagnosis of this rare form of diabetic neuropathy. A few cases of diabetic neuropathic cachexia have been reported in the literature and are briefly reviewed here.